The Role of Artificial Intelligence in Enhancing Risk Management and its Impact on the Effectiveness of School Crisis Response among Middle School Principals in Kuwait - Al-Ajmi, Falah Dhuwaihi Al-Swairi (Journal of Cultural Analysis and Social Change, 2025)
This study aimed to explore the role of artificial intelligence in enhancing risk management and its impact on the effectiveness of addressing school crises among middle school principals in Kuwait. The focus was particularly on understanding how the integration of artificial intelligence technologies can improve risk management strategies, thereby assisting school leaders in making more informed and effective decisions during critical times. To achieve the study's objectives, a descriptive analytical approach was employed, applied to a random sample of 75 middle school principals in Kuwait. Data was collected through carefully designed questionnaires aimed at exploring the levels of artificial intelligence usage, the effectiveness of risk management practices, and the principals’ capabilities in confronting school crises. The results showed that the levels of artificial intelligence usage, risk management, and crisis confrontation among middle school principals were rated at a moderate level, indicating a significant role for artificial intelligence in enhancing risk management. Additionally, it was found that there were no statistically significant differences in the responses of the sample members based on the variables of gender, academic qualification, and years of experience, suggesting that these factors do not markedly influence the use of artificial intelligence in this context. In light of these results, it is recommended to focus efforts on increasing awareness of the concept of artificial intelligence and its benefits in the context of middle school management.